Application of the decision tree, as the weak point of the HACCP system development - Hegedűs, László (Acta Agraria Debreceniensis, 2009)
In this article we have compared the „decision tree” method –suitable for the CCP determination during the HACCP systemintroduction – with the objective measurement method. We have found out, that the CCP-s from the two method differ from each other. So, the empirical „decision tree” method is suitable for determination of CCP-s only limited, while the measurementbased method determines the CCP-s objectively. Only the right CCP-determination can guarantee safe food.